The many facets of perceived bladder health in women: Absence of symptoms and presence of healthy behaviors across the life course - Lisa Kane Low; Beverly Rosa Williams; Diane K. Newman; Jeni Hebert-Beirne; Sonya S. Brady; Deepa R. Camenga; Aimee S. James; Jean F. Wyman; D. Yvette Lacoursiere; Kathryn L. Burgio (Continence)
Purpose:: Qualitative studies exploring bladder health are rare compared to research focusing on lower urinary tract symptoms (LUTS). Our aim was to explore adolescent and adult women’s perceptions about what constitutes a healthy bladder. Methods:: We conducted a 7-site focus group study of bladder health with adolescent and adult women across six age categories (11–14 to 65+ years). Transcripts were analyzed using transdisciplinary, directed content analysis and an iterative interpretive consensus building approach to identify key constructs, focusing on “healthy bladder” and “unhealthy bladder” codes. Results:: Forty-four focus groups with 360 participants were completed. Three thematic categories were identified: (1) concept of a healthy bladder (conceptual abstraction); (2) experience of a healthy bladder (subjective experience); and (3) lifestyle and life course considerations (bladder health in context). Participants struggled to define the unfamiliar concept of healthy bladder and relied on contextualized experiences and behaviors for characterizing bladder health. They described the concept of a healthy bladder as something that you did not need to think about but did require attention to healthy habits to maintain. Other features of a healthy bladder discussed include having bladder control despite urgency and environmental constraints on voiding, normal voiding frequency, and qualities of urine and urination. Participants struggled with lack of information about healthy bladder habits and noted absence of routine bladder health screening. Discussion:: Findings identify need to promote public education and information sharing in health care visits about bladder health. Further they can inform bladder health promotion and clinical research on LUTS prevention.